Factors influencing the price paid for bulls at central test stations in Kansas from 1988-1992 - Simms, D.D.; Schwenke, J.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Results of 13 sales of Angus (n=185) and Simmental (n=544) bulls at central bull tests in Kansas from 1988 through 1992 were analyzed to determine the relationship between performance and the price received. The Kansas bull test index (based 50% on weight per- day-of-age and 50% on test ADG) was the most significant single factor determining price in both Angus and Simmental bulls. Birth weight, final weight, and frame score were other major contributors to price in Angus bulls, whereas weaning weight ratio, birth weight, and being polled were important in Simmental bulls. Expected progeny differences made small but significant (P<.05) contributions in Angus bulls but not in Simmental bulls.
Keywords: Beef; Bull tests; Expected progeny differences